Amino acid composition and crude protein values of some Cyanobacteria from Çanakkale (Turkey). - Akgül, Rıza; Kızılkaya, Bayram; Akgül, Füsun; Erduğan, Hüseyin (My University, 2015)
Cyanobacteria (blue-green algae) form an important component of integrated nutrient managements in agriculture and are exploited in commercial biotechnological ventures. In this study, Rivularia bullata (Poir) Berkeley ex Bornet & Flahault, Nostocs pongiaeforme C. Agardh ex Bornet & Flahault were researched for their amino acid composition and crude protein values. R. bullata was collected from coastal zones of the Gulf of Saros and N. spongiaeforme from the Ayazma Stream. The levels of amino acids were measured in algae samples using EZ: fast kits (EZ: fast GC/FID Protein Hydrolysate Amino Acid Kit) by gas chromatography. The crude proteins of samples were determined by the Kjeldahl method and were calculated using a nitrogen conversion factor of 6.25. Thirty-two amino acids were investigated, for N. spongiaeforme eight free essential amino acids (EAA), eight free non-essential amino acids (NEAA) and eleven other amino acids (OAA); for R. bullata eight EAA, eight NEAA and eight OAA were detected. Aspartic acid is the major constituent for both species. The total protein percents were determined for N. spongiaeforme as % 19.83 and for R. bullata as % 6.15. When considering the increasing world population and reducing natural products; Cyanobacteria will benew feed sources for all living.
Keywords: Bacterial Proteins; Turkey; Amino Acids; Cyanobacteria; 6. Clean water